2000
DOI: 10.2151/jmsj1965.78.4_333
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Profiles of Latent Heat Release and Their Retrieval for TOGA COARE Convective Systems using a Cloud Resolving Model, SSM/I, and Ship-borne Radar Data

Abstract: Latent heating profiles associated with three TOGA COARE active convective episodes (December 10-17 1992; December 19-27 1992; and February 9-13 1993) are examined using the two-dimensional version of the Goddard Cumulus Ensemble (GCE) Model, and retrieved by using the Goddard Convective and Stratiform Heating (CSH) algorithm. The following sources of rainfall information are input into the CSH algorithm: Special Sensor Microwave Imager (SSM/I), shipborne radars and the GCE model. Diagnostically determined l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 55 publications
(72 reference statements)
7
53
0
Order By: Relevance
“…The large rainfall amounts over these regions as shown in Fig. 1e are consistent with strong heating in the atmosphere, indicating dominant role of LH to the total Q 1 (e.g., Tao et al 1993a;Olson et al 1999). It is noted that the mean heating patterns in the two EC models bear larger amplitudes than those by TRMM estimates.…”
Section: Data and Approachsupporting
confidence: 62%
See 1 more Smart Citation
“…The large rainfall amounts over these regions as shown in Fig. 1e are consistent with strong heating in the atmosphere, indicating dominant role of LH to the total Q 1 (e.g., Tao et al 1993a;Olson et al 1999). It is noted that the mean heating patterns in the two EC models bear larger amplitudes than those by TRMM estimates.…”
Section: Data and Approachsupporting
confidence: 62%
“…The two TRMM LH products employed in this study are based on ''trained'' radiometer heating (TRAIN; Grecu and Olson 2006;Grecu et al 2009) and the convective-stratiform heating (CSH; Tao et al 1993bTao et al , 2000Tao et al , 2001 algorithms. The former utilizes both TRMM precipitation radar (PR) and microwave imager (TMI), while the latter only uses the PR.…”
Section: Data and Approachmentioning
confidence: 99%
“…Additional information like cloud contents, vertical motion, and the fall speed of precipitation particles has been also used in partitioning methods (e.g. Tao et al, , 2000Sui et al, 1994;Xu, 1995;Lang et al, 2003). Lang et al (2003) conducted a comparison study using six different partitioning methods based on surface rain-rate, mass fluxes, apparent heating and moistening, hydrometeor contents, reflectivity and vertical velocity CFAD (Contoured Frequency with Altitude Diagram), microphysics, and latent heat retrieval (Churchill and House, 1984;Caniaux et al, 1994;Steiner et al, 1995;Xu, 1995;Lang et al, 2003), and showed that the method based on surface rain-rate was consistently the most stratiform whereas the method based on radar information below the melting level and the fall speed of precipitation particles was consistently the most convective.…”
Section: Discussionmentioning
confidence: 99%
“…Convectivestratiform rainfall partitioning schemes have been developed based on the amplitude and spatial variations of radar reflectivity or surface rainfall rate in previous studies (e.g., Churchill and Houze 1984;Caniaux et al 1994;Steiner et al 1995). Additional information such as the cloud mixing ratio, vertical motion, and fall speeds of precipitation particles have been also used in separation schemes (e.g., Tao et al , 2000Sui et al 1994;Xu 1995;Lang et al 2003). Thus, the convective-stratiform rainfall partition may introduce uncertainty.…”
Section: Introductionmentioning
confidence: 99%